(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2023)
Background: Mother’s Milk (ASI) is the best food for babies. The percentage of coverage of babies aged 0-6 months who get exclusive breastfeeding in 2021 in Indonesia is 54%. The East Banjarmasin District has an increased percentage of exclusive breastfeeding coverage from 54.90% in 2020 to 60.80% in 2021. Efforts to increase milk production can be carried out by non-pharmacological methods, namely consuming katuk leaves in the form of Cookies. Objective: To analyze the effect of giving Katuk Leaf Cookies on increasing milk production in postpartum mothers at PMB MO Banjarmasin. Methods: The research method uses an analytic observational type with a case control research design. The sample used a purposive sampling technique of 12 postpartum mothers in February 2023 at PMB MO. Collecting data using observation and analyzed using the chi square test. Results: Of the 12 respondents, the categories of mothers who were given and not given Katuk Leaf Cookies were 6 people (50%) each, mothers whose milk production increased by 8 people (66.7%). There is an effect of giving Katuk Leaf Cookies on increasing milk production in postpartum mothers at PMB MO Banjarmasin (pvalue = 0.001 <0.05). Conclusion: There is an effect of giving Katuk Leaf Cookies on increasing milk production in postpartum mothers at PMB MO Banjarmasin.